The Analysis of Public Perception of The Buka Luwur Tradition in Sunan Muria and Sunan Kudus Cemetery - Mohammad Khasan; Badik Atul Alieffah; Alifiana Rochmatul Aisyah; Chaerani Astri Hasanah; Jihan Tika Putri (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2024)
This study aims to provide a comprehensive account of the local community’s perspective on the Buka Luwur tradition in two distinct cultural contexts, specifically in Sunan Kudus and Sunan Muria. The research methodology employs a qualitative phenomenological approach. The informants were selected using a purposive sampling technique based on two criteria: (1) caretakers of the graves of Sunan Muria and Sunan Kudus, and (2) native residents of Kudus who participate in the ritual of breaking luwur at their graves. This investigation involved a total of four informants. Data collection employs in-depth interviews. The research employs a direct interview technique, using an interview guide based on the theory of perception characteristics. Coding is used for data analysis, and triangulation establishes credibility. According to the research findings, the Kudus community generally has a favorable perception of the Buka Luwur tradition in Sunan Muria and Sunan Kudus. The people believe that participating in the tradition will result in receiving blessings from the mullah.